Thyroid Hormones Characteristics and Hepatic Deiodinase Enzyme Activity in Broiler Lines Selected for Growth and Feed Conversion - Rahimi, G. (International Journal of Poultry Science, 2005)
The present study was carried out to investigate the influence of genotypes on endocrine parameters in broiler chickens selected for fast growth or better feed conversion rate during the early growth phase. The thyroid hormones levels, hepatic deiodinase enzymes and thyroid hormone receptor activity were analyzed in plasma and hepatic cells of broiler chickens. Age-related changes in plasma T4 and T3 levels were observed. The decrease of plasma T3 levels as a function of age was correlated with relative growth rate. The positive relation between T3 levels and relative growth rate supports the idea that the greater synthesis of this anabolic hormone may be required for the increase in efficiency of protein deposition in chickens at younger ages. In contrast to plasma T3 concentrations, plasma T4 levels increased gradually with age. Analysis of the T3 concentration showed a tendency for higher plasma T3 levels at week 4 and significantly higher at week 7 on the GL compared to the FC line. The plasma T4 concentration in growth selected line was higher in general, and statistically significant at week 4 and 7 of age. The present data show that the decrease of T3 as a function of age is associated with a decrease in type I deiodinase activity. Analysis of deiodinase enzymes showed a non-significantly higher type I deiodinase activity in the fast growing than in the slow growing line at week 4 and 7 of age. A significant age differences were found in type I deiodinase activity within the GL line with lower hepatic type I deiodnase activity at week 7 compared to week 4. No line differences were found in specific binding activity, binding capacity and binding affinity constant between lines, which may indicate that the receptor configuration does not differ among the lines. With this finding, it may be concluded that the hepatic T3-receptor characteristics have not been influenced by the selection criteria that has been used to create these divergent lines.